Chemoradiotherapy screening in a novel biomimetic polymer based pancreatic cancer model. Issue 71 (17th December 2019) - Gupta, Priyanka; Totti, Stella; Pérez-Mancera, Pedro A.; Dyke, Eleanor; Nisbet, Andrew; Schettino, Giuseppe; Webb, Roger; Velliou, Eirini G.
Abstract : Poly-urethane scaffold based 3D pancreatic cancer model enables realistic long term chemotherapy and radiotherapy screening. This model can be used for personalised treatment screening. Abstract : Pancreatic Ductal Adenocarcinoma (PDAC) is a deadly and aggressive disease with a very low survival rate. This is partly due to the resistance of the disease to currently available treatment options. Herein, we report for the first time the use of a novel polyurethane scaffold based PDAC model for screening the short and relatively long term (1 and 17 days post-treatment) responses of chemotherapy, radiotherapy and their combination. We show a dose dependent cell viability reduction and apoptosis induction for both chemotherapy and radiotherapy. Furthermore, we observe a change in the impact of the treatment depending on the time-frame, especially for radiation for which the PDAC scaffolds showed resistance after 1 day but responded more 17 days post-treatment. This is the first study to report a viable PDAC culture in a scaffold for more than 2 months and the first to perform long-term (17 days) post-treatment observations in vitro . This is particularly important as a longer time-frame is much closer to animal studies and to patient treatment regimes, highlighting that our scaffold system has great potential to be used as an animal free model for screening of PDAC.